A Flipped Classroom Approach in Undergraduate Anatomy and Physiology: A Mixed Methods Study Evaluating Learning Environment and Student Outcomes - Gaines, Scott Edward (Curtin University, 2021)
Anatomy and physiology courses are considered a cornerstone of biomedical education. However, many feel they are not adequately preparing students for clinical coursework. One potential solution is the implementation of a flipped classroom approach. Flipped classrooms, however, create an entirely new learning paradigm for the student. The purpose of this explanatory, sequential, mixed-methods study is to explore how the flipped classroom format impacts the attitudes, perceptions, and learning outcomes of undergraduate anatomy and physiology students.